PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP TINDAKAN PAJAK AGRESIF (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Saras Meilia Puspitasari, 13.05.52.0261; Wahjudi, Djoko (Students Journal of Accounting and Banking, 2016)
The research has aim to analiza about independent commisaris, audit commite, institusional owner, the zise of company, leverage, and profitability impact on tax aggressive in manufaktur company that resistered at Bursa Efek Indonesia (BEI). The population in this research is all manufaktur company that registered at Bursa Efek Indonesia (BEI) in year 2012-2014. Taking sample done by using method purposive sampling and the quantity of sample ove 198. The method of taking secunder data that used was documentation of data analized by using multiple regression linear model. The result of research show that profitability have a negative and significant impact on tax aggressive, the zise of company and leverage have a positive and significant impact on tax aggressive. While independent commisaris, audit commite, and institusional owner donât have a significant impact on tax aggressive.Keywords: Independent Commisaris, Audit Commite, Institusional Owner, Size Of Company, Leverage, Profitability, Tax Aggressive